THE INTERDISCIPLINARY RELATIONS OF FORENSIC MEDICINE WITH OTHER SCIENCES - Haydarova Nargizaxon Axtamjon kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine, also known as legal medicine, is a multidisciplinary science that serves the legal system by applying medical knowledge to criminal and civil law. Its integration with various scientific disciplines ensures the accuracy, objectivity, and effectiveness  of  investigations  and  legal  proceedings.  This  paper  explores  the interrelationship  between  forensic  medicine  and  other  sciences  such  as  pathology, toxicology,  genetics,  psychology,  criminology,  and  law.  Understanding  these connections enhances the capabilities of forensic experts and contributes to justice.